2021
DOI: 10.1111/jog.14635
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell degeneration associated with endometriosis of abdominal wall after cesarean section: A case report and systematic review of literature

Abstract: Aim The scar of cesarean section (CS) is the most common site of abdominal wall endometriosis (AWE), whose tumor degeneration has been reported in an increasing number of cases; the most frequent histological type is clear cell carcinoma (CCC). Methods We conducted a systematic research of the literature, collecting data regarding the evidence on tumor degeneration from AWE after CS. Moreover, we reported a case of clear cell borderline tumor (CCBT) originating from AWE. Results We included data of 37 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…However, in this study, the risk of ovarian cancer is not increased in case of peritoneal or DIE. Ferrari et al 14 reported a case of clear cell carcinoma in a parietal endometriosis lesion (post-cesarean section and transverse laparotomy), while Chen et al 15 reported two cases of high-grade serous cancer (HGSC) in an endometriosis of the utero-sacral ligament, followed by Johnson et al 16 and Song et al, 17 each of whom reported a case of HGSC from in a rectal endometriosis. If we add the cases of cervical and rectal degeneration associated with Lynch syndrome, 18 and vaginal degeneration associated with endometrial cancer, 19,20 there are less than 10 cases of degeneration described in the literature (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the risk of ovarian cancer is not increased in case of peritoneal or DIE. Ferrari et al 14 reported a case of clear cell carcinoma in a parietal endometriosis lesion (post-cesarean section and transverse laparotomy), while Chen et al 15 reported two cases of high-grade serous cancer (HGSC) in an endometriosis of the utero-sacral ligament, followed by Johnson et al 16 and Song et al, 17 each of whom reported a case of HGSC from in a rectal endometriosis. If we add the cases of cervical and rectal degeneration associated with Lynch syndrome, 18 and vaginal degeneration associated with endometrial cancer, 19,20 there are less than 10 cases of degeneration described in the literature (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 6 cases, the mean time from the most recent pelvic surgery to diagnosis of clear cell carcinoma of abdominal wall was 20.2 years (18). There is no specific marker for malignant transformation and radiological findings are not helpful in distinguishing abdominal wall endometriosis from its degeneration [ 11 , 19 ]. As a result, lesions usually reach large size at the time of diagnosis with an average diameter of 11 cm [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients are primarily treated with wide tumor resection to obtain healthy margins combined with total hysterectomy and bilateral salpingo-oophorectomy [ 7 , 11 , 22 ]. Bilateral pelvic and inguinal lymph node dissection along with infracolic omentectomy may also be performed [ 18 ] in addition to adjuvant chemotherapy and radiotherapy [ 3 , 11 , 18 , 19 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Locally advanced cancer at the time of diagnosis can explain the poor prognosis of malignant AWE [17]. Some authors describe other prognostic factors such as the size of the mass at the time of diagnosis, which could play a role in a better outcome, especially if the masses range between 4 and 9 cm [63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Prognosismentioning
confidence: 99%